2017
DOI: 10.1136/medethics-2016-103881
|View full text |Cite
|
Sign up to set email alerts
|

Family presence during resuscitation: extending ethical norms from paediatrics to adults

Abstract: Many families of patients hold the view that it is their right to be present during a loved one's resuscitation, while the majority of patients also express the comfort and support they would feel by having them there. Currently, family presence is more commonly accepted in paediatric cardiopulmonary resuscitation (CPR) than adult CPR. Even though many guidelines are in favour of this practice and recognise potential benefits, healthcare professionals are hesitant to support adult family presence to the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
0
24
1
4
Order By: Relevance
“…As such, family preferences and their “right” to be with their loved one during resuscitation also needs to be considered when deciding to allow or deny FPDR. Research tells us that many families believe they have a “right” to be with their loved ones during resuscitation (Giles et al., ; Oczkowski, Mazzetti, Cupido, & Fox‐Robichaud, ; Paplanus, Salmond, Jadotte, & Viera, ; Vincent & Lederman, ), as do clinicians who support FPDR (Oczkowski et al., ). Some experts go further to say clinicians should prioritise family preferences for FPDR due to consistently low survival rates (Lederman et al., ; Timmermans, ; Vincent & Lederman, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, family preferences and their “right” to be with their loved one during resuscitation also needs to be considered when deciding to allow or deny FPDR. Research tells us that many families believe they have a “right” to be with their loved ones during resuscitation (Giles et al., ; Oczkowski, Mazzetti, Cupido, & Fox‐Robichaud, ; Paplanus, Salmond, Jadotte, & Viera, ; Vincent & Lederman, ), as do clinicians who support FPDR (Oczkowski et al., ). Some experts go further to say clinicians should prioritise family preferences for FPDR due to consistently low survival rates (Lederman et al., ; Timmermans, ; Vincent & Lederman, ).…”
Section: Discussionmentioning
confidence: 99%
“…() debated “who should decide” to allow or deny FPDR using the principles of autonomy, beneficence and what they termed the authenticity principle to guide their discussion. More recently, Vincent and Lederman (, p1) argued that the “ethical norm” of allowing FPDR for paediatric patients should also be extended to adult patients. However, we could only locate two primary studies that had undertaken an in‐depth exploration into decision‐making around FPDR (Giles et al., ; Twibell, Siela, Riwitis, Neal, & Waters, ), and we could not locate any studies specifically exploring the role of beneficence in decision‐making around FPDR.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the literature ignores the harsh reality of many out-of-hospital cardiac arrests. Guidelines, [11][12][13] ethical analyses, [14][15][16][17][18] and the rest of the significant literature [18][19][20][21][22] primarily discuss autonomy issues concerning family involvement during CPR. Inevitably, though, family members are likely first responders.…”
Section: Before During and After Cprmentioning
confidence: 99%
“…The controversy surrounding FPDR first emerged in the literature in the early 1980s when a hospital in Mississippi described a situation in which two family members demanded to be present during the resuscitation of their loved ones [6]. Studies of FPDR have shown that family members and staff who were involved in resuscitations report positive attitudes about the practice [1][2][3][7][8][9]. In one study, the majority of family members reported being able to understand the therapeutic interventions performed, to advocate for their child, and to calm or reassure their child during such an event [1].…”
Section: The Debate Over Family Presencementioning
confidence: 99%
“…In addition, the view that FPDR is not in the patient's best interest is not supported by the literature, as parents who have been present during resuscitations have reported decreased anxiety, a better understanding of their child's condition, and a desire to be present again during their child's medical care [1, 6-8, 10, 12]. Nevertheless, clinician attitudes and beliefs about FPDR still remain a source of contention [7].…”
Section: Treatment Team Perspectivementioning
confidence: 99%